2020
DOI: 10.1002/jdd.12180
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of inter‐ and intra‐rater reliability using digital dental software for prosthodontics crown preparations

Abstract: Introduction Since the introduction of the digital dental assessment systems, there has been a shift towards this trend as it appears to provide a more accurate, reliable, time efficient, and reproducible assessment. The Planmeca Emerald scanner coupled with Romexis Compare software allows students and staff to objectively assess individual crown preparations, receive numerical values of key dimensions, and subsequently undergo comparison with ideal crown preparation dimensions. Objectives To measure the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…An investigation of intra-and inter-rater reliability using the Planmeca Emerald IOS and Romexis Compare software showed greater agreement in inter-rater measurement for anterior teeth. The intra-rater measurements showed relative consistency in the results [19]. Unfortunately, only anterior teeth were examined in this study, making it di cult to compare to the present results for posterior teeth.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…An investigation of intra-and inter-rater reliability using the Planmeca Emerald IOS and Romexis Compare software showed greater agreement in inter-rater measurement for anterior teeth. The intra-rater measurements showed relative consistency in the results [19]. Unfortunately, only anterior teeth were examined in this study, making it di cult to compare to the present results for posterior teeth.…”
Section: Discussionmentioning
confidence: 73%
“…Grading can be easily reproduced with the same objective unbiased results and therefore can prevent disagreement between students and instructors about the grades awarded. Moreover, it can be a time saver for lecturers [19]. Students can further improve their practical skills through the constant feedback [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may allow us to consider implementing digital assessment in preclinical operative education without compromising quality of education. Previous studies have also shown promising results of digital assessment compared with conventional assessment as a more accurate evaluation tool 13,19‐22 . Callan et al demonstrated that CAD/CAM presented a high level of precision to analyse the tooth preparations 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown promising results of digital assessment compared with conventional assessment as a more accurate evaluation tool. 13,[19][20][21][22] Callan et al demonstrated that CAD/CAM presented a high level of precision to analyse the tooth preparations. 23 Similarly, other studies showed that CAD/CAM precision was comparable to, 24 or even greater 9,25 than the conventional assessment performed by faculty members.…”
Section: Discussionmentioning
confidence: 99%